Feasibility Study Of Development Telecommunication Devices Repair Business In Cambodia - Gradytio Rahmadi Hartadji; Budi Praptono; Ima Normalia Kusmayanti (eProceedings of Engineering, 2020)
ABSTRACT PT. X has been operating since 2002, located in South Jakarta. PT. X is a national private company engaged in contractors such as construction of BTS (Base Transceiver Station), Transmission, Microwave, Maintenance of BTS (Base Transceiver Station), and Repair BTS (Base Transceiver Station). From 2002-2019 PT. X succeeded in working on many projects related to it is field and has been trusted by various providers throughout Indonesia. At present the owner wants to expand his area of operations to Cambodia to increase profits. After obtaining data to conduct research, the results of BTS development forecasts showed an annual increase of (3%) in 3 providers in Cambodia. In determining the technical aspects, the location, layout of PT. X in Cambodia, and also the standard operation procedure of PT. X. The financial aspects that take into account of income and expenses in cash flow, the estimated amount of income, the amount of operating costs, the need for investment funds, and profit and loss, to calculate the sensitivity aspects include investment feasibility such as Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP) with a set period of 15 months. The results of these calculations show that the level of investment in NPV is 1.069.005,72 USD, IRR is 45%, and the number of months spent until returning to initial capital is 15 months. Due to the results of NPV> 0, IRR 45%> MARR and PBP <Investment period, the repair service of PT. X is declared feasible. Keywords: Feasibility Analysis, Net Present Value (NVP), Internal Rate of Return (IRR), Pay Back Period (PBP).